To Improve Student Engagement in Vocational Education: An Action Research of Beijing Polytechnic in China - Lin, Qianqian; Seongdok Kim (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This action research aimed to enhance student engagement by fostering students’ interest, attention, relevance, confidence, and interaction. There were three objectives of this research: to investigate the current situation of major of art and design student engagement at Beijing Polytechnic (BP); to design and implement appropriate ODIs (Organization Development Interventions) to develop student engagement; to determine the differences in students’ interest, attention, relevance, confidence, interaction, and student engagement between pre-ODI and post-ODI. The sample was 68 students from the School of Art and Design majoring in media design at BP. The quasi-experiment group was exposed to ODIs. The same questionnaire was administered before and after ODI to determine the change level. A mixed methods research was adopted to analyze the data and test the hypotheses. The paired-sample t-test demonstrated whether there was a statistically significant difference in five variables between pre-ODI and post-ODI. The ODIs implemented in this current research included appreciative inquiry (AI), goal setting (GS), differentiated instruction (DI), and team building (TB). The qualitative analysis was conducted to analyzing AI, TB, DI, GS reflection report, and classroom observations used ATLAS.ti software program. Findings from qualitative research methods proved improvement in all variables between the pre-and post-ODI. Based on the findings, critical recommendations concerning the enhancement of student’s interest, attention, relevance, confidence, interaction, and engagement in the BP were put forward to sustain the momentum. Also, recommendations for future research were discussed